Application of Robotics Project-Based Learning to Improve Elementary School Student's Technological Literacy - breva yunanda, anton; Kridoyono, Agung; Sidqon, Mochamad; Yuwono, Istantyo (Universitas Nahdlatul Ulama Surabaya, 2024)
This research aims to analyze the effectiveness of project-based learning in increasing technological literacy in elementary school students. Activities were carried out for three months for 25 class V students at SDN Margorejo 1 Surabaya. The material includes an introduction to basic electronic components, sensors, and simple robot assembly such as line follower and obstacle avoidance. The research used a mixed-method approach with a one-group pretest-posttest design. The main instruments are a technology literacy test and a participatory observation sheet. The results showed an increase in the average score from 48.2 (pretest) to 78.4 (posttest), with the t-test results showing significance (p < 0.05). Qualitatively, students show high enthusiasm, increased curiosity, as well as collaborative and problem-solving abilities. These results indicate that robotics project-based learning is effective in increasing the technological literacy of elementary school-aged children and is worthy of being integrated into basic STEM learning.